Mewujudkan Stabilitas Keuangan Perbankan Syariah melalui Optimalisasi Manajemen Aset dan Liabilitas - Husnia, Nidaul (Maliki Interdisciplinary Journal, 2025)
Sharia banking in Indonesia faces big challenges in managing assets and liabilities in the era of globalization and developments in information technology. This article discusses the importance of asset and liability management (ALMA) in the context of Islamic banking, which functions to optimize the use of funds and ensure financial stability. By using an approach based on sharia principles, ALMA helps banks manage risk and improve asset quality, which is crucial for attracting customers. The application of fund gap management techniques is relevant in maintaining a balance between assets and liabilities. The research results show that effective management can maximize profits while adhering to sharia principles, so that sharia banks can operate sustainably in a competitive industry